DESIGNING AN ARABIC VOCABULARY TEST BASED ON THE ACTFL (AMERICAN COUNCIL ON THE TEACHING OF FOREIGN LANGUAGES) STANDARDS FOR THE NOVICE LEVEL - Mahmudi, Ihwan; Ismail, Moh; Resmalasari Dewi, Neng Rosi; Istibsyaroh, Nailul; Islamanda, Herlinda Sofyan; El-Fani, Aisya Rahma (Abjadia : International Journal of Education, 2024)
This study aims to design an Arabic vocabulary test based on the American Council on the Teaching of Foreign Languages (ACTFL) standards for the novice level. Utilizing the framework established by ACTFL, the test is designed to measure the mastery of basic vocabulary relevant to daily communicative needs at the novice level. The research methodology includes analyzing the needs of novice learners, selecting appropriate words, and crafting questions that cover various aspects of vocabulary comprehension and usage in real-life contexts. The results of the study indicate that the designed test effectively assesses the vocabulary skills of novice learners, with adequate validity and reliability. This test is expected to serve as a useful evaluation tool for Arabic language instructors in assessing learners' progress according to ACTFL standards.